Improving handovers across a North London Mental Health Trust. Issue 2 (28th October 2013) - Perry, Jennifer; Manghnani, Reena; Sommerlad, Andrew; Ikkos, George
Abstract: The GMC Survey June 2011 highlighted that trainees in Barnet, Enfield and Haringey Mental Health Trust (BEH-MHT) were dissatisfied with the Trust's handover process. At this time there were no Trust guidelines on handovers. A quality improvement project was developed to create a consistent out of hours handover process and to improve staff satisfaction thereafter. Handover guidelines were implemented throughout the Trust on 1/2/12. An audit was carried out to measure staff compliance with handovers. A questionnaire was sent out to staff before and after implementation of the guidelines to assess satisfaction with handovers. The audit results highlighted that handovers occurred relatively consistently across the Trust following implementation of the guidelines. The questionnaire results showed an improvement in staff satisfaction with the handover process. The clinical implication of this project is an improved process of out of hours handover across BEH-MHT.